SYNTHESIS OF SULFONATED OLEIC DIESTER GEMINI SURFACTANT USING MICROWAVE ASSISTANCE FOR ENHANCED OIL RECOVERY APPLICATIONS - Ragil, Mochamad
Enhanced Oil Recovery (EOR) is applied to alter the characteristics of reservoir fluids and rocks to decrease residual oil saturation (Sor), consequently increasing oil recovery. In Indonesia, the EOR method being developed is chemical injection, particularly surfactant injection. Anionic sulfonate-based surfactants are suitable for use in Indonesian oil fields due to their excellent performance in sandstone reservoirs and high temperature stability. Gemini surfactants, a type of surfactant that has a dimeric structure, are also widely used in EOR because they are found to have several better characteristics than monomeric surfactants. In organic synthesis, microwaves can be utilized to accelerate reaction processes. This research aims to synthesize sulfonated oleic diester gemini surfactant using microwave assistance for EOR applications. Sulfonated oleic diester gemini surfactant were synthesized using microwave assistance through two sequential reactions, esterification between oleic acid and PEG 200 catalyzed by p-toluenesulfonic acid (pTSA) resulting in polyethylene glycol dioleate (PDO), and PDO sulfonation by chlorosulfonic acid resulting in polyethylene glycol dioleate disulfonate (PDODS). Thin Layer Chromatography (TLC) tests showed that the synthesized PDO and PDODS were pure products. IR spectra of PDO and PDODS showed ester functional groups through peaks of C=O stretching vibrations at wavenumbers of 1742 and 1736 cm–1, respectively. The presence of O-H stretching peaks in the IR spectra of PDODS at wavenumbers of 3040 3740 cm–1 could occur due to absorbed water in PDODS. Sulfonation process was confirmed by the presence of S=O stretching peaks in the IR spectra of PDODS at a wavenumber of 1110 cm–1. PDO and PDODS structures were confirmed by 1H-NMR and 13C-NMR spectra. Surfactant performance tests showed that PDODS surfactant at salinities of 3000 and 6000 ppm stably formed a single phase and was capable of forming microemulsions with Field X and Y oils. The lowest interfacial tension value was achieved by 2% (w/w) PDODS surfactant at a salinity of 6000 ppm against Field Y oil at 2,10 × 10–2 mN/m. 2% (w/w) PODODS surfactant with a salinity of 6000 ppm was able to produce 63% and 58% oil from Field X and Field Y respectively. Based on overall tests, PDODS surfactant shows promising potential for EOR application.